'It kinda sucks': Illness perception of a group of South African adolescents with type 1 diabetes mellitus - Schvaugn Lesage; Elmari Deacon; Esmé van Rensburg; David Segal (AOSIS, 2021)
Background: Living with diabetes is challenging, especially for adolescents at risk of poor glycaemic control. Understanding the illness perceptions of this group is important to be able to develop interventions for this growing population in need. Aim: This study explored the illness perception amongst adolescents living with type 1 diabetes (T1D) and how these perceptions interacted with the management of T1D. Setting: This study was conducted at a medical centre providing care for adolescents living with T1D in Parktown, South Africa. Methods: A qualitative, explorative design with semi-structured interviews was followed. A non-random purposive sampling method was utilised. The illness perception amongst eight adolescents, aged 12-18 years, at risk of poor glycaemic control, was analysed through thematic analysis. Results: Two subthemes related to illness perception were generated, namely (1) illness perception of T1D is negative and (2) living with T1D leads to a sense of being different. Furthermore, two subthemes were generated in relation to how illness perceptions interacted with diabetes management, namely (3) management of T1D is challenging and (4) management of T1D is motivated by fear. Conclusion: This group of adolescents with at-risk glycaemic control believed that T1D is difficult to manage, leading to a largely negative perception of the disease. This study contributes to the body of literature on adolescents where illness perception may play a role in adhering to diabetes care plans. This research may give additional insights into the awareness of illness perception in designing successful interventions.